2012
DOI: 10.1118/1.4718571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of image quality on calcification detection in digital mammography

Abstract: Microcalcification detection was found to be sensitive to detector and dose used. Standard measurements of image quality were a good predictor of microcalcification cluster detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 38 publications
5
70
0
Order By: Relevance
“…This finding is in accordance with previous observer performance study results [1,11]. However, with the use of a higher energy X-ray spectrum obtained with a W/Ag combination, depiction of microcalcifications improved, due to the increase in detector dose level and associated lower quantum noise level.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in accordance with previous observer performance study results [1,11]. However, with the use of a higher energy X-ray spectrum obtained with a W/Ag combination, depiction of microcalcifications improved, due to the increase in detector dose level and associated lower quantum noise level.…”
Section: Discussionsupporting
confidence: 82%
“…It was proposed by Visser et al 7 that premium view increased the suspiciousness of normal and benign structures as well as malignant structures leading to no significant difference in diagnostic accuracy. Also, in the study by Warren et al 10 no significant difference in detection of calcification clusters was found between different image processing algorithms. On the other hand, this result differs from previous work by Zanca et al 6 which had a similar study design.…”
Section: Discussionmentioning
confidence: 90%
“…There have been a number of previous studies investigating the effect of image processing on cancer detection, including both preference studies 2,3 and objective studies. [4][5][6][7][8][9][10] However, the effect of the difference in image appearance resulting from using different image processing algorithms on the detection of the various radiological features of breast cancer is still unclear. The purpose of this work was to perform an observer study to investigate whether the application of different image processing to digital mammograms has a significant impact on the detection of non-calcification cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold gold thickness is compared to European Standards [8] to determine if a system meets the minimum and achievable image quality standards. It has been shown that the threshold gold thickness measured with the CDMAM phantom is predictive of calcification detection [7,8], and, to a lesser extent, mass detection [8]. Studies have investigated if the CDMAM curves from raw images can be predicted from CDMAM curves with processed images [9].…”
Section: Introductionmentioning
confidence: 99%